Design and virtual evaluation of a customized surface-guided knee implant. (October 2016) - Pejhan, Shabnam; Bohm, Eric; Brandt, Jan-Mels; Wyss, Urs
Although total knee arthroplasty is generally a successful operation, many studies have shown that it results in significant alterations in the kinematics of the joint, which cause limitations in performing the activities of daily living. This study aimed to define the design features for a customized surface-guided total knee replacement and to evaluate the kinematic outcomes. Magnetic resonance imaging data of the knee joint are used to generate the design features as they relate to the functionality of the implant. The motion is guided by considering a partial ball and socket configuration on the medial condyle and varying radii of curvature on the lateral articulating surface. A virtual simulation of the behavior of the surface-guided total knee replacement was performed to investigate the motion patterns of this total knee replacement under gait and squatting loading conditions. Results of the virtual simulation show that flexion and extension of the knee make the center of the lateral condyle move more naturally in the posterior and anterior directions, in comparison to the center of the medial condyle. Such guidance is achieved as a result of the novel customized designed contact between the articulating surfaces. The proposed customized surface-guided total knee replacement provides patterns of motion close to the expected more natural target, not only during a gait cycle but also as the knee flexes to higher degrees during squatting. Major design features include location and orientation of the flexion and pivoting axes, the trace of the contact points on the tibia, and the radii of the guiding arcs on the lateral condyle.